Correlation Between the Hepatic Expression of Human MicroRNA hsa-miR-125a-5p and the Progression of Fibrosis in Patients With Overt and Occult HBV Infection - Coppola, Nicola; Onorato, Lorenzo; Panella, Marta; de Stefano, Giorgio; Mosca, Nicola; Minichini, Carmine; Messina, Vincenzo; Potenza, Nicoletta; Starace, Mario; Alessio, Loredana; Farella, Nunzia; Sagnelli, Evangelista; et al. (Frontiers in Immunology, 2018)
ABSTRACT Aims. To evaluate the correlation between the hepatic expression pattern of hsa-miR-125a-5p and HBV-DNA and the progression of fibrosis in patients with overt or occult HBV infection. Methods. We enrolled all the HBsAg positive treatment naive patients (overt HBV group) and all the HBsAg negative patients with hepatocellular carcinoma and with a positive HBV-DNA in their hepatic tissue (occult HBV group), who underwent a diagnostic liver biopsy between April 2007 and April 2015. Tissue concentrations of HBV-DNA and hsa-miR-125a-5p were then analysed by real-time quantitative PCR. Necroinflammatory activity and fibrosis were evaluated according to the Ishak score. Results. During the study period, we enrolled 64 patients with overt and 10 patients with occult HBV infection. In the overt HBV group, 35 out of 64 (54.7%) showed a mild fibrosis (staging 0-2), 17 (26.6%) a moderate fibrosis (staging 3-4), while the remaining 12 (18.7%) had a cirrhosis. All patients in the occult HBV group were cirrhotic. Patients with more advanced fibrosis stage showed a higher mean age as compared to those with mild (p<0.00001) or moderate fibrosis ( p<0.00001) and were more frequently male than patients with staging 0-2 (p=0.04). Similarly, patients with occult B infection were older than HBsAg positive patients. Liver concentrations of miR-125a-5p were significantly higher in patients with cirrhosis (9.75+4.42 AU) as compared to patients with mild (1.39+0.94, p=0.0002) or moderate fibrosis (2.43+2.18, p=0.0006), and were moderately higher in occult than in overt HBV infection. (p=0.09). Moreover we found an inverse correlation, although not statistically significant, between the tissue HBV-DNA levels and the staging of fibrosis. Conclusions. This study suggests a correlation between the tissue expression of hsa-miR-125a-5p and the progression of liver damage in a group of patients with occult or overt HBV infection. If confirmed, these data suggest the hsa-miR-125a-5p may be a novel biomarker of hepatic damage